Nucleation of Amyloid Oligomers by RepA‐WH1‐Prionoid‐Functionalized Gold Nanorods. (4th August 2016) - Fernández, Cristina; González‐Rubio, Guillermo; Langer, Judith; Tardajos, Gloria; Liz‐Marzán, Luis M.; Giraldo, Rafael; Guerrero‐Martínez, Andrés
Abstract: Understanding protein amyloidogenesis is an important topic in protein science, fueled by the role of amyloid aggregates, especially oligomers, in the etiology of a number of devastating human degenerative diseases. However, the mechanisms that determine the formation of amyloid oligomers remain elusive due to the high complexity of the amyloidogenesis process. For instance, gold nanoparticles promote or inhibit amyloid fibrillation. We have functionalized gold nanorods with a metal‐chelating group to selectively immobilize soluble RepA‐WH1, a model synthetic bacterial prionoid, using a hexa‐histidine tag (H6). H6‐RepA‐WH1 undergoes stable amyloid oligomerization in the presence of catalytic concentrations of anisotropic nanoparticles. Then, in a physically separated event, such oligomers promote the growth of amyloid fibers of untagged RepA‐WH1. SERS spectral changes of H6‐RepA‐WH1 on spherical citrate‐AuNP substrates provide evidence for structural modifications in the protein, which are compatible with a gradual increase in β‐sheet structure, as expected in amyloid oligomerization.